Promises to keep : a novel - Rossiter, Nan Parson (Rossiter, Nan Parson. Savannah skies, 2021)
"Thirty-four-year-old Maeve Lindstrom loves her job at Willow Pond Senior Care. Her older sister Macey thinks Maeve is the only human being on earth who can make working in a nursing home sound like fun. Maeve enjoys being around the sundowners, as she calls them, helping them navigate their senior years--brightening a time that can be, all too often, a lonely, sad stage of life. Thirty-three-year-old Gage Tennyson--who brings his mischievous yellow Lab, Gus, to whatever restoration job he is working on with Macey's husband, Ben--loves Maeve with all his heart. He's a handsome country boy and a true southern gentleman. But as he and Maeve grow closer, they both sense that they haven't been completely forthcoming about their pasts. When Maeve realizes Gage might be planning to propose, she knows she must finally be honest with everyone she holds dear. She can no longer live with the secret she's been dragging around like an anchor, and she knows the only way she will be free to build a lifetime relationship with Gage is to risk everything--including his (and her family's) love and respect. Before she finds the courage, however, her past comes careening into her life in a shocking and unexpected way."--Provided by publisher.